Wireless landslide precursor system using vibration sensor / Ahmad Afandi Ahmad Razif - Ahmad Razif, Ahmad Afandi (2011)
This paper presents the design and the implementation of wireless landslide precursor system by using vibration sensor. This project is based on wireless technology. RF module is used for mediation of the two mediums. A shock sensor is used to detect the vibration. This project is to develop a source code in MPLAB programming. This wireless landslide precursor system is being control by a microcontroller, which is PIC16F877A type act as the brains for the system. The sensor will be connected to PIC Microcontroller. The controller is programmed to determine which sensor is detecting the vibrations and give signal to RF transmitter module. RF transmitter module then transmits data to RF receiver module. RF receiver module receives a signal.